FEATURES OF DIVISION OPERATIONS BY PROGRAMMABLE LOGIC INTEGRATED CIRCUITS - Опанасенко, В. М.; Лісовий, О. М.; Сорока, Є. В. (Science-based technologies, 2009)
The dividers blocs on PLD base of type of FPGA were developed. They were realized by behavior description on VHDL. The functioning of dividers blocs was checked by simulation method in ModelSim Xilinx Edition — MXE III and behavior stand.